Project coordination study of shareBIM on structural skeletal of a reinforced concrete building - Chong, Weng Khuen (2022)
Building Information Modelling (BIM) is implemented to improve coordination, planning, and management processes. The coordination and planning of BIM have been proven to reduce the communication and material procurement issues faced in the construction industry. This study aims to model and quantify a project building's structural model and to describe how important ShareBIM functions as a communication platform during the design phase to complete the study. The objectives of this study are to model the structural framing in the Autodesk Revit model; quantify the beam, column, and slab elements; and perform a statistical analysis of concrete, rebar, and shear link costs and quantities. A set of high-rise reinforced concrete building drawings has been used as a reference to achieve the aim and objectives in this study. A 3D skeleton model is built in Autodesk Revit and exported to ShareBIM to conduct a collaboration check of clash issues between MEP and the architectural model. The finalized model has been conducted structural analysis in Esteem 9, then compute quantity take-off and perform statistical analysis for the cost and quantities of concrete, rebar, and shear links. In short, structural material procurement was computed at a value of RM3.314 million for this building. This study helps to reduce any uncertainties and arguments during actual construction.